Evaluating the Effectiveness of Interactive Multimedia in Boosting Brand Equity: A Case Study of Visual Communication Design Programs - Purhita, Edy Jogatama; Rudjiono, Daniel (University of Science and Computer Technology, 2024)
This study focuses on strengthening brand equity in the Visual Communication Design (VCD) study program at higher education institutions by implementing interactive multimedia. The background of the problem lies in the importance of branding innovation in addressing the increasing competition in the education sector. The purpose of this research is to evaluate the impact of interactive multimedia on four dimensions of brand equity: brand awareness, brand loyalty, perceived quality, and brand associations. The methodology employed involves a mixed quantitative and qualitative approach. Data was collected through a survey of 100 respondents using a Likert-scale-based questionnaire and in-depth interviews with relevant participants. A paired t-test was used to analyze changes in brand equity perceptions before and after implementing interactive multimedia. The results show a statistically significant increase in brand awareness by 20% (p < 0.01), brand loyalty by 25% (p < 0.01), perceived quality by 18% (p < 0.01), and brand associations by 19% (p < 0.01). These findings provide practical contributions to higher education institutions by demonstrating that interactive multimedia is not merely a communication tool but an effective strategy for building emotional engagement with audiences and enhancing institutional reputation. Furthermore, qualitative insights highlight the role of interactive multimedia in fostering deeper emotional connections and improving perceptions of quality. This research supports adopting technologies like Augmented Reality (AR) and Virtual Reality (VR) to enrich future learning experiences. Continuous implementation and innovation in interactive content are also necessary to remain relevant and competitive in the dynamic education market.